Designing programs - Keelan, M.
On a lot of questions of coaches in concern of designing training programs for weightlifters, e.g. - How many days each week does the weightlifter train? - How many sessions will the lifter endure? What combination of exercises should be used? Should the emphasis be on technique, power, speed, or strength? - How much rest is required between sets or workouts ? - What happens if the lifter shows signs of breaking down?